A comparative study on the comprehensive properties of natural microfibers isolated from the large-clustered bamboos in the southwest of China using steam explosion. Issue 1 (31st December 2023) - Li, Qiushi; Su, Ganmao; Chai, Xijuan; Xie, Linkun; Zhou, Juying; Du, Guanben; Zhang, Lianpeng; Wang, Siqun; Xu, Kaimeng
ABSTRACT: To develop sustainable functional fibers and expand their novel applications, the large-clustered dendrocalamus sinicus (DS) and the dendrocalamus giganteus (DG) planted in the southwest of China were effectively isolated by steam explosion (SE). The fine and uniform bamboo microfibers of DS and DG corresponding to the smallest average widths of 18.24 μm and 17.16 μm were obtained, respectively. The relative content of cellulose in two bamboo species had a marked increase after SE but a decrease for hemicellulose and lignin without any introduction of toxic chemical reagents. The SE treatment improved the thermal stability, the crystallinity, and the surface hydrophilicity of bamboo samples with their morphologies varying from rod-shaped strips to fibrous filaments. The degrees of crystallinity for DS and DG increased from 57.63% and 57.53% to 73.67% and 74.10%, respectively. The thermal stability, mechanical properties, and hydrophobicity of bamboo microfibers derived from DS were superior to those of DG, which showed a higher maximum decomposition temperature (5.24°C), tensile strength (181 MPa), elongation at break (1.1%), and water contact angle (7.8°).